SISTEM PENDUKUNG KEPUTUSAN KENAIKAN PANGKAT DI SMA NEGERI 1 LEMBANG JAYA KABUPATEN SOLOK MENGGUNAKAN METODE PROFILE MATCHING - Eko Amri Jaya; Indah Febriyani; Suci Rahmadhani (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2019)
SMA Negeri 1 Lembang Jaya is one of the schools located in Solok Regency and at the moment the promotion process for honorary teachers is still using the manual system, so it requires a long time to fill in the promotion data. Therefore, SMA Negeri 1 Lembang Jaya needs a new system to make it easier to fill data to make it more effective and efficient. Decision support systems using the Profile Matching method are designed to assist decision making in problems solving that are semi-structured or unstructured. This decision support system was built using the Visual Basic 6.0 programming language, Microsoft Office Access as a support for data storage media, and Crystal Report. With this decision support system, it is easier for schools to make promotions for honorary teachers.The Profile Matching method will provide more accurate information for promotions by rating according to established criteria.